Monitoring of water quality with HPLSEC and fluorescence method in the ozonated recirculating aquaculture system - Pettersson, Samu; Ignatev, Alexey; Lindholm-Lehto, Petra; Tuhkanen, Tuula (Springer Science and Business Media LLC, 2023)
In recirculating aquaculture systems (RAS), it is important to monitor the water quality to keep the fish healthy. Especially in water treatment with oxidizing agents, for example, ozone (O3) or hydrogen peroxide (H2O2), the monitoring of the quality of dissolved organic matter (DOM) in water is advisable to keep track of the treatment’s effect. Previously in wastewater treatment plant (WWTP) studied, HPLSEC and fluorescence method for monitoring and characterization of organic matter was used here to track the effect of oxidative treatments; 5 duplicated treatments (2 × O3, 1 × O3 + H2O2, 1 × H2O2, 1 × control) were performed for four months with weekly samplings. Systems that contained O3 injection reduced fluorescence on average over 90%, except tyrosine-like fluorescence with removal of 80%. Combined O3 + H2O2 treatment did not bring any advantages over pure O3 treatment, and H2O2 had no significant effect on fluorescence. Humic and fulvic compounds were detected to largely be derived from inlet lake water, while large protein-like structures were mostly created in RAS. A peak of benzoic acid-like molecules was also detected in all RAS waters. Treatments did not change the molecular weight profile of DOM systems and inlet water, having most of their fluorescence coming from medium-sized (108–1322 Da) molecules. DOC was lower in O3 treatments, but the linear connection between DOC and fluorescence was not observed, although this was proposed in earlier studies. Most likely, the oxidizing treatments induce change to DOM in a way that such comparison becomes inaccurate, although this must be studied further in the future.
Keywords: Advanced oxidation process; Fluorescence; High-performance size exclusion chromatography; Hydrogen peroxide; Natural organic matter; Oxidative treatment